Production disruption management for R/M integrated supply chain using system dynamics methodology - Qiaolun Gu; Tiegang Gao (International Journal of Sustainable Engineering, 2017)
The impacts of production disruption in Remanufacturing/Manufacturing (R/M) integrated supply chain on the sales and the methods of production disruption management were studied. A system dynamics model for the R/M integrated supply chain with production disruption was improved by system dynamics methodology. The numerical examples were shown to illustrate the simulation results. The impacts of different recovery times of production disruption on the sales were presented. In order to mitigate the disruption risks and ensure the sales at the needed sales ratio, the methods for setting multi-echelon inventory levels before the occurring of the production disruption and the methods for making back-up plans after the production disruption occurs were given.